Dissolved and soluble pore water trace metals (Cd, U, V, Cu, As, Mo) from sediment core SO268/1_79-1 (MUC-19) during SONNE cruise SO268/1, central Pacific - Paul, Sophie Anna Luise; Schmidt, Katja; Koschinsky, Andrea (In: Paul, Sophie Anna Luise; Schmidt, Katja; Achterberg, Eric Pieter; Koschinsky, Andrea (2024): Pore-water and solid-phase trace metals from sediment cores during SONNE cruises SO268/1 and SO268/2, central Pacific [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.965035, 2022)
Physical and chemical trace metal speciation are important for our understanding of metal cycling and potential toxicity to marine life. Trace metals can have different bioavailability and behave differently in diffusion processes or particle-solution interactions depending on their physical and chemical forms. Here we investigated dissolved (< 0.2 µm) and soluble (< 0.02 µm) concentrations of Mn, Co, Cu, V, Mo, U, Cd, and As in oxic and suboxic deep-sea sediments of the central equatorial Pacific. Vanadium, Mo, U, Cd, and As showed no significant difference between the dissolved and soluble concentrations suggesting that they are present as inorganic ionic species or organic complexes either in the truly dissolved or small colloidal fraction. The same was true for Mn and Co in suboxic pore waters. In contrast, the colloidal fraction (> 0.02 µm < 0.2 µm) of Cu increased with depth. Samples were taken during the SO268 cruise to the German and Belgian license areas for polymetallic nodule mining in the Clarion Clipperton Fracture Zone as part of the MiningImpact project. Sediment cores were collected with multicorers (MUC), ROV push cores (PUC), and gravity corers (GC). Pore water was extracted by means of centrifugation and sequential filtration using cleaned polyethersulfone (PES) syringe filters (0.2 µm) and Anopore syringe filters (0.02 µm). Pore water was preserved by acidification to ~ pH 1.8 with concentrated ultrapure HCl. Samples were measured by Inductively Coupled Plasma-Mass Spectrometry.
Keywords: CCZ; Pacific; pore water; size fractionation; trace metals